Persistence of different fungicides used against Alternaria alternata in tomato - and M.P. THAKUR, S.S. CHANDRAVANSHI, B.P. SINGH (Indian Phytopathology, 2002)
The residual effect of systemic and non-systemic fungicides on seed and other plant parts was studied for varying periods against Alternaria alternata (Fr.) Keissler causing leaf blight of tomato. Seed treatment with different fungicides showed persistence of carbendazim for 90 days. Non-systemic fungicides applied on foliage persisted for 10 days. Systemic fungicides like Aliette persisted in roots and leaves of tomato seedlings upto 23 days while thiophanate methy 1 and carbendazim remained for 19 days after soil application. Leaf extracts of treated plants were more inhibitory than similar extracts from roots to A. alternata.